The Extractive Industries Transparency Initiative (EITI) and the Technical Reforms model: Insights from the Global Performance Assessments literature. Issue 4 (December 2021) - Fenton Villar, Paul
Highlights: The EITI lacks a sufficient theory of change. There is scope to understand the role of the EITI secretariat in its theory of change. The EITI secretariat's country assessments may contribute to the technical reforms model. The GPA literature highlights the hawthorne effects and reputational, aspirational, and competitive motivations they can illicit from governing elites. Abstract: The Extractive Industries Transparency Initiative (EITI) is now widely recognised as a leading development policy helping govern the production of oil, gas, and other mined materials. This study builds on recent theoretical work conceptualizing how the EITI might reach its long-term goals of improving natural resource governance and promoting inclusive forms of social and economic development. While existing discussions describe the need to explore how these conceptual models might work within specific national contexts, this paper highlights there is also scope to further understand them from an international perspective by looking at the role of the international EITI secretariat. Drawing on a review of the broader literature dedicated to Global Performance Assessments, it presents an example elaborating on how the international secretariat's country assessments may affect what is known as the Technical Reforms model (a model describing the EITI may help to improve the governance of natural resources by strengthening the regulations that manage them). Overall, this discussion highlights the EITI's country assessments may encourage the adoption of reforms due to the Hawthorne effects and reputational, aspirational, and competitive motivations they can illicit from governing elites.